Answer:
1) (2x + 2)(x + 2)
2) 2(x + 1)(x - 1)
3) (x^2 + 3)(x^2 - 3)
4) 2x(x + 5)(x - 2)
5) (5x + 2y)(5x - 2y)
Step-by-step explanation:
1)
2x^2 + 6x + 4
= 2x^2 + 4x + 2x + 4
= 2x(x + 2) + 2(x + 2)
= (2x + 2)(x + 2)
2)
2x^2 - 2
= 2(x^ 2 - 1) (The difference of two squares)
= 2(x + 1)(x - 1)
3)
x^4 - 9 (The difference of two squares)
=(x^2 + 3)(x^2 - 3)
4)
2x^3 + 6x^2 - 20x
= 2x(x^2 + 3x - 10)
= 2x(x + 5)(x - 2)
5)
25x^2 - 4y^2 (The difference of two squares)
= (5x + 2y)(5x - 2y)
Answer:
lets start with the division
10/10
1
3+2 . 1 - 1
5 . 1 - 1
5. 1 = 5
5 - 1 = 4
Step-by-step explanation:
The answer is -4
Solution:
f(x) = 3x - 7
g(x) = 2x^2 - 3x + 1
(fog)(0)
= f(2(0)^2 - 3(0) + 1)
= f(2x^2 - 3x + 1)
= f(1)
= 3x - 7
= 3(1) - 7
= -4
Answer:
about an hour and 42 minutes
Step-by-step explanation:
Time=Distance/Speed
Answer:
is that a song you write cause it is good
Step-by-step explanation: